The Impact of Donor Age on Survival After Heart Transplantation: An Analysis of the United Network for Organ Sharing (UNOS) Registry. Issue 5 (19th July 2014) - Weber, Daniel J.; Wang, I‐wen; Gracon, Adam S. A.; Hellman, Yaron M.; Hormuth, David A.; Wozniak, Thomas C.; Hashmi, Z. A.
Abstract Background Data are limited regarding the influence of donor age on outcomes after heart transplantation. We sought to determine if advanced donor age is associated with differences in survival after heart transplantation and how this compares to waitlist survival. Methods All adult heart transplants from 2000 to 2012 were identified using the United Network for Organ Sharing database. Donors were stratified into four age groups: 18–39 (reference group), 40–49, 50–54, and 55 and above. Propensity scoring was used to compare status IA waitlist patients who did not undergo transplantation with IA recipients who received hearts from advanced age donors. The primary outcome of interest was recipient survival and this was analyzed with multivariate Cox regression analysis and the Kaplan–Meier method. Results A total of 22, 960 adult heart transplant recipients were identified. Recipients of hearts from all three older donor groups had significantly increased risk of mortality (HR, 1.187–1.426, all p < 0.001) compared to recipients from donors age 18 to 39. Additionally, propensity‐matched status IA patients managed medically without transplantation had significantly worse adjusted survival than status IA recipients who received hearts from older donors age ≥55 (HR, 1.362, p < 0.001). Conclusions Compared to donors aged 18–39, age 40 and above is associated with worse adjusted recipient survival in heart transplantation. This survival difference becomes more pronounced as age increases to above 55. However, the survival rate among status IA patients who receive hearts from advanced age donors (≥55) is significantly better compared to similar status IA patients who are managed without transplantation. doi: 10.1111/jocs.12406 (J Card Surg 2014;29:723–728)